Exploring the Role of Humor as a Coping Component in Marital Satisfaction - Benali, Youssef; Hernández, Carlos; Novak, Mateja (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore how humor functions as a coping mechanism that contributes to marital satisfaction among couples in Slovenia.Methods and Materials: A qualitative design was employed, relying on semi-structured interviews to capture couples’ lived experiences of humor in marriage. Twenty-four participants (12 couples) from Slovenia, married for at least three years, were recruited using purposive sampling. Interviews were conducted until theoretical saturation was achieved, with each session lasting between 60 and 90 minutes. Data were transcribed verbatim and analyzed thematically using NVivo 14 software. Trustworthiness was enhanced through peer debriefing, member checking, and triangulation with field notes.Findings: Four major themes emerged from the data: (1) Humor as an Emotional Buffer, where couples described humor as a strategy for stress relief, emotional recovery, and conflict de-escalation; (2) Humor and Intimacy, highlighting the role of shared jokes, playful teasing, and affectionate humor in strengthening closeness and trust; (3) Humor as a Communication Strategy, with participants explaining how humor allowed them to soften criticism, indirectly express sensitive issues, and repair conflicts; and (4) Humor and Marital Resilience, where humor facilitated coping with external stressors, fostered perspective-taking, and sustained hope during challenges such as illness or financial strain. Couples reported that affiliative and self-enhancing humor styles were most beneficial, while aggressive humor could undermine satisfaction. Humor was also noted as increasingly expressed through digital interactions, including memes and messaging.Conclusion: The findings suggest that humor is a multidimensional coping resource in marriage, functioning simultaneously as an emotional, relational, communicative, and resilience-enhancing tool. While humor generally promotes marital satisfaction, its effects depend on style and context. These insights highlight the importance of constructive humor in maintaining healthy, satisfying, and enduring marital relationships.